Regulation of Platelet Aggregation by Post-fibrinogen Binding Events - Peerschke, Ellinor I (Thrombosis and Haemostasis, 1995)
A variety of data suggest that fibrinogen binding is necessary but not sufficient for platelet aggregation: post fibrinogen binding events may play an important role. The present study compared fibrinogen binding and platelet aggregation in response to dithiothreitol (DTT) and ADP. DTT induced saturable and specific fibrinogen binding (Kd 0.07 + 0.02 μM, Bmax 15,000 + 3000 molecules/platelet) which supported complete platelet aggregation as determined by single platelet counting. The aggregates were small, however, and more readily dissociated by EDTA than their ADP-treated counterparts, despite quantitatively similar fibrinogen binding. Unlike fibrinogen bound to ADP-stimulated platelets, fibrinogen bound to DTT-treated platelets remained sensitive to dissociation by EDTA over a 3 h time course, retained its ability to support aggregation, even when aggregation was induced 60 min after the initial platelet exposure to fibrinogen, and remained accessible to polyclonal antibodies and plasmin. Confocal scanning laser microscopy showed only surface clustering of fibrinogen bound to DTT-treated platelets over the 3 h time course compared to rapid fibrinogen clearing from the surface of ADP-stimulated platelets. These data suggest that post fibrinogen binding events involved in the stabilization of fibrinogen binding and/or the redistribution of bound fibrinogen may play important roles in regulating platelet aggregation.